2022
DOI: 10.23919/jcn.2022.000004
|View full text |Cite
|
Sign up to set email alerts
|

MobiRPL: Adaptive, robust, and RSSI-based mobile routing in low power and lossy networks

Abstract: Article that has been accepted for inclusion in a future issue of a journal. Content is final as presented, with the exception of pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Moreover, the authors in [19] designed a method called MobiRPL in which they suggested an adaptive time out for DIO to detect the disconnection more quickly. They also produced an adaptive probing mechanism to check the connectivity and a proactive discovery mechanism to discover new parents by sending specific DIS messages.…”
Section: A Reactive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors in [19] designed a method called MobiRPL in which they suggested an adaptive time out for DIO to detect the disconnection more quickly. They also produced an adaptive probing mechanism to check the connectivity and a proactive discovery mechanism to discover new parents by sending specific DIS messages.…”
Section: A Reactive Methodsmentioning
confidence: 99%
“…The RSSI determines the link quality in the MSE method, and a threshold is defined based on the RSSI value to determine the boundary between the confidence zone and the critical zone. Similarly, some previous methods utilized the concept of RSSI-based defined zones in different ways and functionalities [19,21].…”
Section: Critical and Confidence Zonesmentioning
confidence: 99%
“…IEEE 802.15.4e time-slotted channel hopping (TSCH) [2], a MAC protocol for low-power and lossy network (LLN), is one of those examples. It has been designed to satisfy the growing demand for more reliable and energy-efficient LLNs in emerging Internet of Things (IoT) applications such as industrial IoT [3]- [8], in-vehicle IoT [9], [10], environmental monitoring [11]- [14], home IoT [15], and health IoT [16]- [18]. TSCH brings the benefits of time-slotted communication to LLN, and its channel hopping allows the network to become more robust to external interference or multi-path fading through frequency diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The name "Internet of Things" is regarded a misnomer because gadgets do not need to be linked to the public Internet, only to a network and be individually addressable (Alsulaimani & Islam, 2022). The IoT refers to the network of physical devices, vehicles, home appliances, and other objects embedded with sensors, software, and connectivity that enables these objects to connect and exchange data (Fekete & Kiss, 2023;Kim et al, 2022). This technology allows for increased automation, improved efficiency, and enhanced connectivity between various devices (Qamar, 2023).…”
Section: Introductionmentioning
confidence: 99%